CO2 soil emission under different methods of oil palm replanting (2015)
Colombian oil palm plantations have started a largescalereplanting phase. The replanting process has an effect onthe disposal of biomass, plant health management, and agroecological conditions due to the disturbance that is generated.This document addresses soil respiration (CO2 flux) as a responsevariable of crop replanting. Seven renovation methods used inColombia were tested. The measurements were taken over timeafter the disturbance and planting of the new crop. This study wascarried out in the municipality of Tumaco between August of 2009 and June of 2011 using 7 methods of renovation and 4 stages of crop development. The CO2 flow was measured at 12 points in each plot. There were no significant differences for the CO2 emission among the replanting methods. The average value for respiration was 929 mg CO2 m-2 h-1 (± 270.3); however, significant differences were found over time.This response was not related to fluctuations of soil temperatureand moisture; therefore, there should be an associated responseto biotic factors (microbial organisms) not established in thisstudy. The values suggested that the soil of the plots under areplanting process emitted considerable quantities of carbon intothe atmosphere, but the emissions declined over time and, in turn,were offset by the photosynthesis of the new crop (14 μ CO2 m-2s-1 ± 1.4, data not shown), creating an overall positive carbon balance.